Human Epidermal Growth Factor Receptor 2 (HER2) positive breast cancer is associated with Indigenous American ancestry in Latin American women - Marker, Katie M. (Cancer Res, 2020)
Women of Latin American origin in the United States (U.S.) are more likely to be diagnosed with advanced breast cancer and have a higher risk of mortality than non-Hispanic White women. Studies in U.S. Latinas and Latin American women have reported a high incidence of Human Epidermal Growth Factor Receptor 2 (HER2) positive (+) tumors; however, the factors contributing to this observation are unknown. Genome-wide genotype data for 1,312 patients from the Peruvian Genetics and Genomics of Breast Cancer Study (PEGEN-BC) was used to estimate genetic ancestry. We tested the association between HER2 status and genetic ancestry using logistic and multinomial logistic regression models. Findings were replicated in 616 samples from Mexico and Colombia. Average Indigenous American (IA) ancestry differed by subtype. In multivariate models, the odds of having an HER2+ tumor increased by a factor of 1.20 with every 10% increase in IA ancestry proportion (95%CI 1.07–1.35, p-value 0.001). The association between HER2 status and IA ancestry was independently replicated in samples from Mexico and Colombia. Results suggest that the high prevalence of HER2+ tumors in Latinas could be due in part to the presence of population-specific genetic variant(s) affecting HER2 expression in breast cancer.